6 - Politics of Financialisation and Inequality: Transforming Global Relations for Inclusive Development - Oloruntoba, Samuel (Africa Development, 2021)
Inequality remains one of the most fundamental challenges of the contemporary world. It has become a global phenomenon which affects the underclass, the deprived and the poor both in the global north and south. Despite the advancement in technology which has fueled economic growth and fostered cross-national mobility of factors of production, inequality and its twin, poverty, remain major issues of inquiry among scholars, consideration for policy makers and concern for the poor. Most studies on inequality have been preoccupied with the economic forces. This article locates the growing degrees of inequality in the world within the global politics of financialisation in which the transnational capitalist class (TCC) adopts a reactionary ideology of neoliberalism to further their interest through the creation of massive fictitious wealth, maintenance of stranglehold on domestic and international policy institutions and spreading of the illogic of the sanctity of the market. I argue that capitalism in its current form is unsustainable for the human society. Consequently, the structure of power that informs and maintains the current order must be transformed to foster inclusive development. Despite the resistance to such transformations by the members of the TCC at the core, the process is inevitable due to the internal contradictions within the system itself, the emergence of new loci of power from different regions of the world and increased revolutionary pressures from below. Overall, the article concludes that there is an inextricable link between financialisation and global inequality.